Testing preference of alfalfa hay of different relative feed value and brome hay in lactating Jersey cows - K.K. Buse; P.J. Kononoff (JDS Communications)
Forages comprise a large portion of dairy cattle rations, and quality can have a large influence on feed intake and milk production. Although factors like particle size, fiber content, and digestibility affect it, palatability can also play a role in feed intake. The objective of this study was to conduct an experiment to evaluate the effect of relative feed value (RFV) on feed preference. A taste preference sequential elimination experiment using 16 lactating Jersey cows (210 ± 4 DIM, 27.4 ± 3.24 kg/d milk yield, 19.6 ± 1.52 kg/d DMI; ± SD) was conducted to test this objective. Reduced-lignin alfalfa hay diets with a high RFV (213; HIRFV), mid RFV (163; MDRFV), and low RFV (94; LORFV) were compared with a control smooth brome grass hay (75 RFV; Brome). Cows were offered 0.45 kg of each alfalfa treatment and 0.23 kg of the hay treatment in a randomized arrangement within the feed bunk for 1 h or until the feed was fully consumed or consumed in the greatest amount. Feeds were offered for 9 d with all treatments offered the first 4 d. The most preferred feed was then removed, and the remaining 3 feeds were offered for 3 d. The process was repeated for the last 2 d. Feed preference was ranked from 1 to 4 with 1 being the most preferred and 4 the least; this was in the order they were removed. The rankings of each treatment for each cow were summed and averaged. The probability of a treatment being chosen first was determined using the Plackett-Luce model. The preference ranking of HIRFV was highest (1.06 ± 0.25), followed by LORFV (2.56 ± 0.63), MDRFV (2.75 ± 0.58), and Brome (3.25 ± 0.93). The probability of HIRFV being selected first is 95.7% ± 0.79%, whereas the probabilities of LORFV, MDRFV, and Brome being selected first are 2.09% ± 0.38%, 1.70% ± 0.38%, and 0.55% ± 0.46%, respectively. These results support the notion that higher quality alfalfa hay is preferred by cows. The secondary preference of LORFV could be associated with the presence of byproducts of Maillard reactions, which would lower the RFV while providing more favorable flavors than were present in MDRFV and Brome.